KECENDERUNGAN WAJIB PAJAK ORANG PRIBADI UNTUK MELAKUKAN TAX EVASION: PERSPEKTIF ANALISIS MULTINOMIAL - Yulianti, Nur Wachidah; Afifka, Fina (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
Tax is one of the sources of state revenues that can be used for development and public services. However, the occurrence of tax evasion cases, which still frequently happen, can hinder tax revenue and its realization. Based on this, the research aims to identify the factors that may influence the tendency of Individual Taxpayers (WPOP) to engage in tax evasion. The respondents in this research are individual taxpayers. The number of individual taxpayers sampled in this research is 116. The method used for sample determination is convenience sampling, while the method for data processing is multinomial logistic regression analysis. The results of the multinomial logistic regression indicate that the variables love of money and materialism do not significantly influence the tendency of Individual Taxpayers to commit tax evasion. In contrast, the variables rational attitude and financial condition have a significant impact on the tendency of Individual Taxpayers to engage in tax evasion.